(untitled) - Johnson, Christine (England, 2000)
"Banking and Finance"is one of a number of specialist books within the Market Leader series that compliments the course. Each book consists of 18 units, 2 tests, and a multilingual glossary
Keywords: English language,English language,Banks and banking,English language; Conversation and phrase books (for bank employees),Sound recordings for foreign speakers,Problems, exercises, etc,Business english